Trends and impact of digital marketing on consumer engagement in sustainable business-based fashion e-commerce: A bibliometric approach - Adzahra, Afifa Riflah; Murniati, Murniati (Edelweiss Applied Science and Technology, 2025)
This study employs bibliometric analysis to explore trends and the influence of digital marketing on consumer behavior and engagement within sustainable fashion e-commerce. Focusing on environmental, social, and economic sustainability, the research investigates how digital marketing strategies promote responsible consumption and brand loyalty. Utilizing the Biblioshiny package in R software, the study follows a structured methodology, defining research objectives, sourcing data from Scopus, and applying bibliometric tools. The analysis reveals a consistent annual increase in scholarly interest, highlighting the growing relevance of sustainable fashion e-commerce. It also identifies significant geographic research contributions, particularly from the United States, Indonesia, and Spain. Despite challenges such as limited citation recognition, international collaborations and varied publication formats have advanced the field. The findings emphasize the importance of understanding digital marketing trends to support sustainable practices in the fashion industry. This research offers practical and theoretical insights for academics, marketers, and policymakers seeking to enhance consumer engagement through sustainability-driven digital marketing. Overall, it underscores the critical role of digital marketing in shaping consumer behavior and fostering long-term brand relationships in the context of sustainable fashion e-commerce.